Erratum: Novel Rechargeable Lithium-Ion Battery Based on a Cathode of Potassium-Cobalt(Ii) Octacyanomolybdate (Journal of the Electrochemical Society 2021 168 100543 Doi: 10.1149/1945-7111/Ac3113) - Herrera-Diaz, F; Herrera-Diaz, F (Institute of Physics, 2022)
In the Acknowledgments, the grant number for the funding provided by FONDECYT was incorrectly listed as 1240108. The correct grant number is 1210408. © 2022 Electrochemical Society Inc.. All rights reserved.